2009
DOI: 10.1007/s00526-009-0231-8
|View full text |Cite
|
Sign up to set email alerts
|

Absolute continuity and summability of transport densities: simpler proofs and new estimates

Abstract: The paper presents some short proofs for transport density absolute continuity and L p estimates. Most of the previously existing results which were proven by geometric arguments are re-proved through a strategy based on displacement interpolation and on approximation by discrete measures; some of them are partially extended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 18 publications
(44 reference statements)
1
69
0
Order By: Relevance
“…Several avenues for future research will address remaining theoretical and practical challenges suggested by our work. On the theoretical side, an analog of our analysis may apply to the Beckmann model of transport over R n [1,32], showing how quadratic regularization affects flows in the continuum.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several avenues for future research will address remaining theoretical and practical challenges suggested by our work. On the theoretical side, an analog of our analysis may apply to the Beckmann model of transport over R n [1,32], showing how quadratic regularization affects flows in the continuum.…”
Section: Discussionmentioning
confidence: 96%
“…These algorithms are primarily of theoretical interest but do employ interior point-style methods, possibly implying a systematic choice of flows in the case of multiple optima.In the continuum, the theory of optimal transport [42] classifies problems structured similarly to minimum-cost flow as the 1-Wasserstein distance or Beckmann problem [1]. See [33] for analysis and [42,17,32] for theoretical discussion. Even over general spaces, solutions of the 1-Wasserstein problem generally are nonunique and include some degenerate optima [42, §2.4.6].…”
mentioning
confidence: 99%
“…Indeed, (2) first arose as the "Beckmann problem" in network flow [Beckmann 1952]. See [Santambrogio 2013] for further analysis of this problem and its connection to optimal transportation, and see [Villani 2003, §1.2.3], [Feldman and McCann 2002], and [Santambrogio 2009] for a broader discussion.…”
Section: Optimal Transportationmentioning
confidence: 99%
“…The L p regularity of the transport density σ is proved successively by many authors (see, for instance, [7,8,9,11,18]). In particular, we have the following…”
Section: Introductionmentioning
confidence: 96%